"Sounding" the System: Noise, In/Security and the Politics of Citizenship. (13th August 2021) - Stanley Niaah, Sonjah
Abstract : The instruments of nation, their creators and enforcers (the system) in the postcolonial Caribbean have never been favourable in their intentions toward the way the masses have lived and had their being. In various sectors of life, particularly entertainment, little or no space was made available through this system which included legislative suppression tantamount to cultural erasure. However, another system emerged. Blacks have always had their bodies, creating sounds, often significantly amplified, in contravention of the system supported by state laws. Accounting for systems of eradication which surrounded black entertainment, this article foregrounds the sound system as representation. Sound is used as a signifier, mobilized in opposition to the politics of "noise" and thus an act—as in "sounding", a verb, a philosophy of doing, of resistance, much like "grounding". "Sounding" is articulated as a practice, a form of productive labour, complementary to the labour of citizenship, of nation-building, and celebration of the human. Drawing on examples from Jamaica, and located at the intersection of cultural history, cultural geography, and cultural studies more broadly, this article continues exploration of Black Atlantic performance geography by placing entertainment practice in a wider comparative and analytical field at the heart of sound revolutions across the African Diaspora.